Internationalizing higher education in Malaysia understanding, practices and challenges - Tham, Siew Yean (Institute of Southeast Asian Studies, 2013)
This book examines the understanding, practices and chanllenges that Malaysia's higher education institutions face in their efforts to internationalize higher education at their respective institutions. This issue is of grat importance to academics, policy-makers and students in institutions of higher learning in Malaysia, given the country's aspiration to become a hub for higher education.